-7m-8=-9m+6

Simple and best practice solution for -7m-8=-9m+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7m-8=-9m+6 equation:


Simplifying
-7m + -8 = -9m + 6

Reorder the terms:
-8 + -7m = -9m + 6

Reorder the terms:
-8 + -7m = 6 + -9m

Solving
-8 + -7m = 6 + -9m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '9m' to each side of the equation.
-8 + -7m + 9m = 6 + -9m + 9m

Combine like terms: -7m + 9m = 2m
-8 + 2m = 6 + -9m + 9m

Combine like terms: -9m + 9m = 0
-8 + 2m = 6 + 0
-8 + 2m = 6

Add '8' to each side of the equation.
-8 + 8 + 2m = 6 + 8

Combine like terms: -8 + 8 = 0
0 + 2m = 6 + 8
2m = 6 + 8

Combine like terms: 6 + 8 = 14
2m = 14

Divide each side by '2'.
m = 7

Simplifying
m = 7

See similar equations:

| 3x(2x-1)=-75 | | 8+6x=-4 | | 4(3a-2)=16 | | 20x-2=28+4 | | 7-c=36 | | 4(2x+7)=-7+27 | | 102-5/5 | | 10n+1=6/4 | | x+(x+10)+(4x-31)=969 | | y/4-3 | | x^3+2x=6 | | 6/5-m+2/2=3m+4/6 | | 6*5/14 | | 42=3.5x | | 5(2-j)-(2j-3)= | | 3x-4=1-2x | | 72/140 | | F(0)=x^2+8x+9 | | -8=2x+2+3x | | -3a+6+7a=9a-2a | | 8y-(2y-3)=-14 | | 109-(4x+10)=4(x+9)+x | | -2x-3y=49 | | 2.5x+0.7=4.6-12 | | y=a-2-3 | | X^2+3x-216=0 | | -x+6=-26 | | 6(w+5)=3w+21 | | -6a+3=-3(4a-1) | | 2c/d | | 26x-6-18x+4=23x-3-15x+15 | | 48=x+2(2x) |

Equations solver categories